Covid-19 literacy test: Developing of instruments and measuring for high school students - Ilham Nurseha; Mieke Miarsyah; Rizhal Hendi Ristanto (Biosfer: Jurnal Pendidikan Biologi, 2022)
COVID-19 literacy is very important in dealing with the current pandemic, especially for students who will or are carrying out offline learning. So, it is necessary to develop an instrument that can measure the literacy ability of COVID-19. This study aims to develop an instrument that can assess the COVID-19 literacy level of high school students. The research method used is research and development with Borg & Gall model, which consists of eight stages namely (1) research and initial information collection, (2) designing, (3) developing initial products, (4) expert validation, (5) initial product revision based on input from expert validators; (6) Field trials, (7) revision, (8) implementation and dissemination. The results of the development obtained 28 items consisting of eight questionnaires and 20 multiple choice questions. The questionnaire aims to obtain descriptive data about students' attitudes towards the COVID-19 pandemic, while multiple choice questions are used to measure students' knowledge. The expert test results obtained a score of 3.56 so that the COVID-19 literacy instrument developed was in the very feasible category. In the next stage, the validity of multiple-choice questions was tested and 15 questions were included in the valid category, then the 15 questions obtained were tested for reliability, based on the calculation of the calculated r value greater than r table so that the developed instrument was reliable and could be used in subsequent research.